Species and functional plant diversity enhance ecosystem functions in the central Monte desert. (18th October 2020) - Chaves, Jimena E.; Aranibar, Julieta N.; Gatica, Gabriel
Abstract: Questions: Niche complementarity has been proposed as the underlying mechanism for optimizing resource use of plants in diverse ecosystems, usually associated with their functional traits and not with the species number per se. Our main questions were: (a) does species diversity optimize the use of resources in arid ecosystems; (b) is there redundancy of species in the use of water and nutrients; and (c) what diversity components most affect ecosystem functions of water regulation and material cycling? Location: Central Monte desert, Argentina. Methods: We selected vegetation patches with different species ( SD ) and functional diversities ( FD ), where we measured indicators of water regulation and material cycling. At two soil depths, we measured soil nitrate, phosphate, organic matter, chloride, electrical conductivity, and pH. We also determined decomposition, plant water use efficiency (foliar δ 13 C of C3 plants), and nitrogen use (δ 15 N). These variables were used as response variables, while total plant cover, species richness, Shannon, Simpson, evenness, and Rao's functional diversity indexes were used as predictors. Results: At the soil surface, response variables were better explained by models that included diversity ( SD, FD or both) instead of evenness, total plant cover or null model. A diversity effect was not detected in deeper soil layers for most variables, except for electric conductivity, which had a positive effect on FD . Richness explained plant δ 13 C but had no influence on plant δ 15 N. Conclusions: Diversity of plant community influences ecosystem processes, as it increases decomposition, soil organic matter, and nutrient availability at the surface, and decreases water losses to the subsoil and plant water use efficiency. Both SD and FD explained one or more ecosystem processes of water regulation and material cycling, suggesting that individual species contribute to ecosystem functioning, with a low redundancy for arid areas. Abstract : Species and functional plant diversity improved ecosystem functions of water regulation and material cycling in Monte desert dunes. Diversity increased decomposition, nitrate availability, and soil organic matter, which acidified the soil and increased phosphate availability. Diversity also optimized soil water use, reducing water losses to the subsoil, and plant water use efficiency, suggesting higher water availability in more complex and diverse patches. The importance of both, species and functional diversity in ecosystem functions supports niche complementarity mechanism.